As contribuições de um projeto empreendedor para um grupo de estudantes do ensino médio politécnico - Souza, Paulo Sérgio Souza de (2016)
This thesis presents the stages and results of a qualitative case study research, which aimed at evaluating how a Project on Entrepreneurship may contribute to the formation of a group of Polytechnic High School students. The research comprised 25 polytechnic high school students from a state school in Rio Grande do Sul, Brazil. Data were collected via a semi-structured questionnaire. The productions carried out by the research subjects for the project conclusion were also collected. “Discursive Textual Analysis” was used to analyze data. The analysis results are presented in four categories: the subjects’ perceptions regarding the Entrepreneurship Project, knowledge mobilized and built by the students, attitudes developed via the Entrepreneurship Project, and relationships established via the Entrepreneurship Project. The first category evinced that the subjects saw the project as a challenge, that the project demanded more commitment and more responsibilities, and the students’ acknowledgement that the project promoted important learning. The second category revealed the conceptual and procedural contents which were present in the activities carried out by the students. The third category showed the presence of attitudinal contents developed by the students via their attitudes, as well as the capabilities manifested by the students their productions. The fourth category revealed the relationships among the students, the differences of ideas, teamwork, and the relationships between the teacher and the students. The thesis concludes that the Entrepreneurship Project contributed to the students’ formation, mobilizing and building knowledge by integrating conceptual, procedural and attitudinal contents in different activities, which were contextualized via the theme of entrepreneurship.